Leadership Strength in Decision Making in the Social Services of Sukabumi District - Ade Fahrudin (Jurnal Mantik, 2021)
Leadership style is a factor that influences employee performance at the Social Service of Sukabumi Regency, this is proven by the value of leadership style significantly influences employee performance. Effective communication and decision making also significantly influence employee performance. It is proven by the results of qualitative analysis for effective communication and for decision making, which means that effective communication and decision making have a significant effect on employee performance. Leadership style, effective communication and decision making together have an influence on employee performance. This is indicated by the results of the study so that it can be concluded that leadership style, effective communication and decision making simultaneously affect the performance of Sukabumi district social service employees.